All Questions Topic List
Differential Equation Questions
Previous in All Question Next in All Question
Previous in Differential Equation Next in Differential Equation
Question Number 74821 by sridhar nayak last updated on 01/Dec/19
Answered by mind is power last updated on 01/Dec/19
⇔(6ey−2x)dy−dx=0...Etrytoofindk(y)Tomakitexacte⇔k(y)(6ey−2x)dy−k(y)dx=0∂∂x(k(y)(6ey−2x))=∂dy(−k(y))⇒−2k=−k′⇒k′=2k⇒k=e2yE⇔e2y(6ey−2x)dy−e2ydx=0letF(x,y)=csuchdF=e2y(6ey−2x)dy−e2ydx=0⇒∂F∂x=−e2y⇒F(x,y)=−xe2y+h(y)∂F∂y=6e3y−2xe2y=−2xe2y+h′(y)⇒h′(y)=6e3y⇒h(y)=2e3y+cF(x,y)=−xe2y+2e3y+c=0
Terms of Service
Privacy Policy
Contact: info@tinkutara.com